Ecology, occurrence and distribution of wild felids in Sarawak, Malaysian Borneo - Mohd Azlan, Jayasilan; Sally, Soo Kaicheen; Lok, Lisa Choy Hong; Cheok, Melynda Ka Yi; Maiwald, Marius Joscha; Helmy, Olga E.; Giordano, Anthony J.; Brodie, Jedediah F. (Cambridge University Press, 2022)
Sarawak is the largest state in the megadiversecountry of Malaysia. Its rich biodiversity is threatened byland-use change and hunting, with mammalian carnivoresparticularly affected. Data on the ecology, occurrence anddistribution of small carnivores are crucial to inform theireffective conservation, but no large-scale assessments havepreviously been conducted in Sarawak. Here we examinethe status of the five species of felids in Sarawak based ondata from camera-trap studies overyears (May–February) acrossstudy areas, including protected areasof various sizes, production forests and forest matrix withinoil palm plantations. Felids were detected at%ofcamera stations. The marbled catPardofelis marmorataandSunda clouded leopardNeofelis diardihad higher probabil-ities of occurrence in protected than unprotected areas, andvice versa for the leopard catPrionailurus bengalensisandbay catCatopuma badia. The marbled and bay cats weremostly diurnal, and the leopard cat was predominantly noc-turnal; activity patterns did not substantively differ betweenprotected and unprotected sites. The probabilities of oc-currence of marbled and bay cats increased with greaterdistance from roads. The leopard cat and flat-headed catPrionailurus planicepswere more likely, and the cloudedleopard less likely, to occur near rivers. Flat-headed catspreferred peat swamp forest, bay cats lowland forest, andmarbled cats and clouded leopards occurred in both low-land and montane forest. Felids may tolerate higher eleva-tions to avoid anthropogenic disturbance; therefore, it iscritical to preserve lowland and mid-elevation habitatsthat provide refugia from climate change and the destruc-tion of lowland habitat.